Precarity, precariousness and software workers: wages, unions and subjectivity in the Argentinian software and information services sector. (1st April 2017) - Andrés Rabosto; Mariano Zukerfeld
Abstract : This article focuses on a paradigmatic type of knowledge work: informatics. Specifically, it studies the processes of precarity and precariousness taking place in the Argentinian software and information services (SIS) sector. After a brief introduction, it discusses the relevant literature, introducing the concepts of precarity and precariousness. Then it looks at the data relating to employment, exports and wages in the Argentinean SIS sector before moving on to address a key element for understanding precarity: the complexities of unionisation in the SIS sector. Finally, it analyses precariousness in the sector by attempting to characterise the subjectivities of these workers.